INCOME ANALYSIS OF PEOPLE'S COFFEE FARMERS (COFFEA). IN SIPIONGOT VILLAGE, DOLOK DISTRICT, NORTH PADANG LAWAS DISTRICT - Yanti, Mariana Eva; Nasution, Nurhadida; As’ad, Octasella Ainani; Surbakti, Supriadi (Institute of Computer Science (IOCS), 2023)
North Padang Lawas Regency is one of the largest districts for coffee production centers in North Sumatra, one of which is in Sipiongot Village. Sipiongot Village is the village with the largest coffee production followed by the number of farmers. Sipiongot Village has a small number of farmers. Coffee in Sipiongot Village is relatively low compared to other sub-districts. This can mean that the land area in Sipiongot Village is large, so that to increase the productivity of plants, development can be carried out. In the research, it can also be concluded that coffee production which decreases with decreasing area results in decreasing farmer income. Another cause is the high cost structure of coffee cultivation and post-harvest, resulting in farmers' welfare levels decreasing. Therefore, a problem formulation can be formulated, namely: 1. What is the structure of production costs for coffee farmers in Sipiongot Village. 2. What is the income of coffee farmers in Sipiongot Village? This research uses quantitative methods then income analysis and data analysis. Quantitative analysis is carried out to see the condition of the location, the condition of the farmers. Analyze income channels, and the function of income (marketing). With the research results, the R/C ratio value for cash costs obtained by farmers in Sipiongot Village is IDR. 59,756,078 and the R/C ratio value for total costs is Rp. 68,980,131. This proves that the coffee farming business run by coffee farmers in Sipiongot Village is less profitable.